Transport Economics - Button, Kenneth (London: Heinemann, 1982)
This book is intended to show how modern economics can be applied to the transport sector. Further, it is not concerned with specific modes or forms of transport but rather with the movement of goods and people.
Includes bibliographies and index.
ne 1/03/2018
Loan
Keywords: Transportation